تحليل خصائص اللغة العربية الفصحى المناسبة الوضعية وأنواع الاشتقاق و النحت والأصوات العربية وثبات أصولها: Analisis Ciri-ciri Bahasa Arab Klasik Positifisme, Jenis Derivasi, Seni, Bunyi dan Kestabilan Asal-usul Bahasa - Ismi Istiqomah; Dhoyfun Akbar (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2023)
This research aims to investigate classical Arabic which is divided into two parts, namely Classical and Colloquial Language. Here the researcher explores the characteristics of classical language in terms of situational suitability, grammar, Arabic sounds, and the stability of its origins. The researcher admitted that this research had not achieved maximum results due to a lack of knowledge and information about the characteristics of classical Arabic used by Aljazeera Arabic. The focus is on analyzing the characteristics of Classical Arabic, the development of meaning and language structure. The object of this research is analysis of lexical, grammatical and contextual meaning, as well as syntactic research in the form of phrase, clause and verbal analysis. The theory of this research is al-Nazhariyyah al-Siyaqiyyah or contextual theory developed by J.R Firth. This research uses a type of library research using two approaches, namely sociolinguistic and lexicostatistical approaches. This research reveals that the classical Arabic language used in Arabic books has experienced many developments in meaning and structure and developments in science and technology have also had a major influence on the development of vocabulary in various fields such as politics, economics and science and technology